Social Protection in Fragile and Conflict-Affected Countries : Trends and Challenges - Ovadiya, Mirey (World Bank, Washington, DC, 2015)
This discussion paper is the first output under the umbrella of the programmatic work on social protection in fragile and conflict-affected states. This work aims to develop operational guidance to teams on the likely determinants of effective social protection programming and policy making in fragile and conflict-affected settings. This paper elaborates on the role of social protection programming, and programming design and implementation features, that are prominent in fragile and conflict-affected states. In particular, the paper objectives in these countries, reflects on their revealed objectives, and discusses programming options chosen to achieve those objectives as well as how several countries have overcome particular operational and capacity constraints. This paper presents a methodology that has been devised to group countries based on income, capacity, and extent of enabling environment. Use of this methodology will aid in understanding trends, patterns, and key factors in policy making and programming choices, good and bad.